Pengaruh Pengenalan Lapangan Persekolahan Daring, Persepsi Profesi Guru, Persepsi Kesejahteraan Guru, Teman Sebaya, dan Lingkungan Keluarga terhadap Minat Menjadi Guru (Universitas Negeri Semarang, 2022)
Interest in becoming a teacher is a person's interest in the teaching profession which is indicated by the desire, motivation, and attention of the person that arises based on positive self-reaction and feelings of pleasure. This study aims to analyze and obtain empirical evidence regarding the effect of Online School Field Introduction (PLP), Teacher Profession Perception, Teacher Welfare Perception, Peers and Family Environment on Interest in Becoming a Teacher. The population of this research is the students of the 2018 Accounting Education study program as many as 120 students. Determination of the sample using purposive sampling with the criteria of active students in Accounting Education 2018 who have participated in online PLP and obtained 83 students. The data collection method uses a questionnaire or questionnaire. The data analysis method used descriptive statistical analysis and multiple linear regression analysis using IBM SPSS v24. The results showed that there was an influence of online School Field Introduction (PLP), perceptions of the teaching profession, perceptions of teacher welfare, peers and family environment on the interest in becoming a teacher simultaneously. Then partially there is no effect of the perception of the teaching profession and the perception of teacher welfare on the interest in becoming a teacher in the 2018 UNNES Accounting Education students